Caracterização da produção acadêmico-científica nacional sobre a temática transposição didática - Guedes, Catiane Medianeira Limberger (2020)
This research is carried out within the scope of the INOVAEDUC Research and Extension Group. The work focuses on the presence of Didactic Transposition and the Anthropological Theory of Didactics in academic-scientific research. Therefore, the objective is to present a characterization of the academic-scientific production on Didactic Transposition theme linked to master's dissertations and doctoral theses developed within the scope of Graduate Programs. It is understood that the investigation may contribute to a better understanding of the ways in which these themes are being used in research in the educational field. The present study was guided by the question: What are the main characteristics of academic-scientific works that contemplate the theme of Didactic Transposition and Anthropological Theory of Didactics in the educational area? It is an empirical research, in which academic-scientific work documents, specifically Master's Dissertations and Doctoral Theses, are taken as sources for the collection of information. To collect data relevant to the work, a textual analysis script developed and adopted by the INOVAEDUC group was used as an instrument, consisting of a set of items that must be present in academic-scientific works. The basic guidelines of the so-called Grounded Theory (Theorization Rooted in Information) were used as a guide for the research process. In the collection of documents, the CAPES Thesis and Dissertation Bank was used, searching for the terms "Didactic Transposition" and "Anthropological Theory of Didactics". In this process, works that presented the search terms in the title, abstract or keywords were selected for the study. The sample consists of 57 papers, 40 Master's Dissertations and 17 Doctoral Theses, totaling 57 texts. As a result of the analysis, it became evident that, during the ten years covered by the research, there was a prevalence of publications in the year 2011. The most present curricular component was Mathematics, which used qualitative methodologies and diverse sources and collection instruments. Furthermore, it was concluded that the IES with the largest number of publications was UFMG and the main author referenced by the works that make up the sample of this analysis was Yves Chevallard. The predominant focus of the work is the use of teaching technologies, with the main objective of improving teaching practices. Thereat, it can be said that DT (Didactic Transposition) and ATD (Anthropological Theory of Didactics) are present in research at different levels of education, being used in the works, especially to assist in the transposition of concepts or knowledge.